Digitalization empowers the innovative development of agricultural vocational education - Wang, Jing; Li, ShiYi; Lin, YuHan (LPPM STIKI Malang, 2024)
AI-empowered high-quality innovation and development of agricultural vocational education is a key step to optimize the allocation of agricultural vocational education resources and improve the level of agricultural vocational education, and it is also an inevitable choice to promote the breakthrough development of agricultural innovation. AI as a means of shortcut, with its unique role, is constantly filling the gap of agricultural talents. At the same time, in the process of the continuous integration and development of AI and agricultural vocational education, certain educational risks have also arisen, and how to correctly avoid risks and promote the high-quality innovation and development of agricultural vocational education is a new topic of the times.